Integrated transcriptomic and metabolomic analysis reveals the effects of EMMPRIN on nucleotide metabolism and 1C metabolism in AS mouse BMDMs - Yun Zhang; Diyuan Zhang; Zulong Xie; Tianli Xia; Lili Zou; Tao Wang; Li Zhong; Zhuo Zeng; Lingying Wang; Guozhu Chen; Xing Liang (Frontiers in Molecular Biosciences)
BackgroundExtracellular matrix metalloproteinase inducer (EMMPRIN) has been considered as a key promoting factor in atherosclerosis (AS). Some studies have shown that regulating EMMPRIN expression in bone marrow-derived macrophages (BMDMs) of ApoE−/− mice can affect plaque stability, but the mechanism was not clear.MethodsAS model mice were built from high-fat-feeding ApoE −/− mice, and were divided into siE group and CON group. The BMDMs and aortas from AS mice were harvested following in vivo treatment with either EMMPRIN short interfering (si)RNA (siEMMPRIN) or negative control siRNA. Transcriptomic and metabolomic profiles were analyzed using RNA-sequencing and Liquid chromatography-tandem mass spectrometry (LC-MS/MS), respectively. The efficacy of siEMMPRIN was assessed through real-time quantitative polymerase chain reaction (RT-qPCR) and Western blotting (WB). Immunofluorescence staining was employed to measure EMMPRIN expression within aortic atherosclerotic plaques. Cell proliferation was monitored using the Cell Counting Kit-8 (CCK8), while flow cytometry was utilized to analyze the cell cycle. Additionally, seahorse analysis and oil red O staining were conducted to verify glucose and lipid metabolism, respectively.ResultsA total of 3,282 differentially expressed metabolites (DEMs) and 16,138 differentially expressed genes (DEGs) were identified between the CON group and siE group. The nucleotide metabolism and one-carbon (1C) metabolism were identified as major altered pathways at both the transcriptional and metabolic levels. Metabolomic results identified increased levels of glycine, serine, betaine and S-adenosyl-L-methionine (SAM) to S-adenosyl-L-homocysteine (SAH) ratio and decreased levels of dimethylglycine (DMG) and SAH in 1C metabolism, accompanied by the accumulation of nucleotides, nucleosides, and bases in nucleotide metabolism. Transcriptomics results shown that Dnmt, Mthfd2 and Dhfr were downregulated, while Mthfr were upregulated in 1C metabolism. And numerous genes involved in de novo nucleotide synthesis, pentose phosphate pathway (PPP) and dNTP production were significantly inhibited, which may be associated with decreased BMDMs proliferation and cell cycle arrest in the G0/G1 phase in siE group. Multi-omics results also showed changes in glucose and lipid metabolism. Seahorse assay confirmed reduced glycolysis and oxidative phosphorylation (OXPHOS) levels and the Oil Red O staining confirmed the decrease of lipid droplets in siE group.ConclusionThe integrated metabolomic and transcriptomic analysis suggested that nucleotide metabolism and 1C metabolism may be major metabolic pathways affected by siEMMPRIN in AS mouse BMDMs. Our study contributes to a better understanding of the role of EMMPRIN in AS development.